Stakeholder involvement in the development of trial material for a clinical trial. (14th December 2020) - Rix, Jacqueline; Branney, Jonathan; Breen, Alexander C.; Sewell, Philip; Docherty, Sharon
Abstract: Background: Stakeholder involvement includes not just patients and public, but also those delivering treatment for example clinicians and students. Each stakeholder brings unique experiences to the process. The aim of this stakeholder exercise was to explore readability and understanding of the trial material for the future trial to be conducted by the authors: Biomechanical Effects of Manual Therapy—A Feasibility Study. Design: Volunteers from identified stakeholder groups were provided with trial material which included the information sheet, consent form, questionnaires and home management booklet. They provided feedback on content (readability, understanding) and style (font, layout). An additional document was provided with genres of pictures to choose the most appropriate style to be used in the booklet. Readability formulas were used to calculate reading age before and after feedback to objectively measure ease of reading. Results: The public group provided a layperson's perspective to clarify the information sheet for patients, whereas practitioner and intern groups indicated where information could be clarified. The reading age of all documentation decreased following feedback; however, templated sections of the documentation did not. The majority (87%) of volunteers chose coloured classic cartoons for the booklet. Conclusion: This process highlighted the importance of involving different stakeholder groups in the development of research materials as each group made a unique contribution. Readability and understanding of the trial material were improved, feeding back into the consent process contributing towards fully informed consent. Patient or Public Contribution: Public helped develop materials for a future trial but not with manuscript preparation.